Reducing Electromagnetic Interference in Three-Level T-type Isolated Bidirectional DC-DC Converter Using a Snubber Circuit - Halime HIZARCI; Kemal KALAYCI; Onur DEMIREL; Uğur ARIFOĞLU (International Journal of Applied Methods in Electronics and Computers, 2021)
Electromagnetic interference is the main problem in high switching power converters like DC-DC converters. One of the solution methods for electromagnetic interference reduction is to design a snubber circuit. The snubber circuit is a practical method to reduce fluctuations caused by parasitic components from the layout and non-ideal characteristics of switching devices. An effective snubber circuit design increases the converter’s efficiency and reduces EMI noise. In this paper, electromagnetic interference is reduced using different snubber circuits in a three-level T-type isolated bidirectional DC-DC converter. The converter is simulated in PSIM to see the effectiveness of the noise reduction with the snubber circuits. CISPR 25 standard is used for the compliance assessment in the study.